Medicinal plants diet as emerging complementary therapy from the Amazonian tradition. Data from Centro Takiwasi, a Peruvian therapeutic community. - Politi, Matteo; Rumlerova, Tereza; Saucedo Rojas, Gary; Rumlerova, Tereza; Marcus, Olivia; Torres Romero, Jaime; Mabit, Jacques (Journal of Medicinal Herbs and Ethnomedicine, 2019)
Abstract This article presents data related to the diet-retreat users at Centro Takiwasi, a therapeutic community that specializes in addiction rehabilitation based on a protocol that combines western psychotherapy with traditional Amazonian medicine. Central to Amazonian shamanism in Peru is the dieta (diet-retreat), a practice of drinking plant preparations in isolation in the rainforest while observing dietary restrictions, abstaining from social relations, sexual activities, and the use of perfumes. In the past two decades, the dieta has become increasingly popular among a global audience as an alternative form of healing for various physical and mental health conditions. We discuss socio-demographic data of the diet-retreat users at Centro Takiwasi from 2012-2017, describing as well the main plants used for this medical practice inspired by the local Amazonian traditional knowledge. Results indicate a rising interest in the shamanic diet for westerners as a complementary or integrative therapeutic experience. Moreover, further research on the Amazonian diet could contribute to implement a novel approach in herbal medicine at large.